PENGETAHUAN, SIKAP DAN PERILAKU PADA KASUS DEMAM BERDARAH DENGUE DI KECAMATAN MANDIRAJA TAHUN 2022 - Bayu Suseno; Putri Harfianti (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2022)
Environmentally Based Diseases (PBL) is a health problem that is still common in the world,including in Indonesia, one of the PBLs that is still a problem is DHF. Based on data from theBanjarnegara Health Office, the highest dengue cases in 2020 were in Mandiraja District with 39cases. Based on data from the Mandiraja 2 Public Health Center UPTD, the highest prevalence ofDHF was in Purwasaba Village. The purpose of this study was to determine and describe thedescription of knowledge, attitudes, and behavior in cases of DHF in Purwasaba Village, MandirajaDistrict. This research is included in descriptive research with cross sectional approach. Thepopulation in this study was 63 houses with respondent criteria, namely dengue patients diagnosed inJanuary-March 2022, and local residents with a radius of 200 m in RT 03 RW 03 Purwasaba Village,Mandiraja District, with purposive sampling using sampling. The data used in this study are primarydata obtained from questionnaires and field observations as well as secondary data from previousstudies. Based on the results of the study obtained data that respondents with an age range of 36-45years 31.7%, female respondents 66.7%, most of the respondents' education levels in the study were36.5% elementary school graduates, most of the respondents' occupations were as follows:housewives 42.9%, the knowledge of most of the respondents is good 88.9%, the attitude of therespondents is classified as good 88.9% and the behavior of the respondents is classified as positive55.6%. Based on the results of data processing, it is known that in the case of DHF in PurwasabaVillage, Mandiraja District, they have good knowledge, behave well, and behave positively. Thecommunity further improves behavior regarding PSN DHF and health workers further improvehealth promotion, namely by providing counseling about DHF so that public knowledge about DHFincreases and by holding activities to eradicate mosquito nests.